Inflation by The Einstein-Scalar-Gauss-Bonet Theory with Potential Inflation - Sambiri, Usman; Saputra, Aji (TECHNO: JURNAL PENELITIAN, 2025)
Research has been conducted on the inflation theory by Einstein scalar-Gauss-Bonet theory with inflation potential to study the scenario of inflation. The purpose of this study is to calculate the inflation solution of the ESGB model. The research method used is a literature study with a mathematical approach. In this model, the Gauss-Bonet term is coupled with a scalar field so that it significantly modifies the dynamics of the early universe. The form of the scalar field used is f(Phi) = lambda(Phi)2 and the inflation potential is quadratic, V = (Phi)2 . The lambda values used are 0.1; 0.2; 0.5; 1.0; 2.0; 10. For lambda less than or equal to 0.5, successfully demonstrate the inflationary solution, namely obtaining an exponentially expanding scale factor and a fixed value of the Hubble constant. In addition, the linear e-fold value is obtained by a linear graph and an exponentially decaying scalar field is obtained and an exponentially decaying scalar field is obtained. These results indicate that the ESGB model with inflationary potential can demonstrate the existence of an inflationary solution.